2023
DOI: 10.1111/dom.15068
|View full text |Cite
|
Sign up to set email alerts
|

Association between glycaemia risk index (GRI) and diabetic retinopathy in type 2 diabetes: A cohort study

Abstract: Aim: To investigate the association between a new composite metric, glycaemia risk index (GRI), and incident diabetic retinopathy (DR).Methods: A total of 1204 adults with type 2 diabetes without DR at baseline were included between 2005 and 2019 from a single centre in Shanghai, China. GRI was obtained from continuous glucose monitoring data at baseline. Cox proportion hazard regression analysis was used to assess the association between GRI and the risk of incident DR.Results: During a median follow-up of 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Consistent with these findings, a correlation between the GRI and long‐term diabetic microvascular complications has been demonstrated. In a cohort study involving 1,204 adults with type 2 diabetes, a higher glycemia risk index was associated with an increased risk of incident diabetic retinopathy 13 . Moreover, another study showed that the GRI was strongly associated with albuminuria and was an independent risk factor for macroalbuminuria 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these findings, a correlation between the GRI and long‐term diabetic microvascular complications has been demonstrated. In a cohort study involving 1,204 adults with type 2 diabetes, a higher glycemia risk index was associated with an increased risk of incident diabetic retinopathy 13 . Moreover, another study showed that the GRI was strongly associated with albuminuria and was an independent risk factor for macroalbuminuria 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, researchers also explored the association between the glycemia risk index and diabetes‐related complications. A higher GRI was shown to be associated with an increased risk of incident diabetic retinopathy 13 and albuminuria 14 . However, these studies focused primarily on microvascular complications, and no previous research has investigated the connection between glycemia risk index and macrovascular complications.…”
Section: Introductionmentioning
confidence: 97%
“…Also, the association between GRI and risk of developing long-term diabetes-related complications remains to be fully explored in people with type 1 diabetes though early studies have demonstrated that GRI correlated with the risk of microvascular complications of albuminuria and diabetic retinopathy in patients with type 2 diabetes. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of the present study include the relatively small sample size compared to large data studies; however, this is a real-life cohort with stable control and comprehensive knowledge of glycometric and clinical variables with a single CGM system. The non-incorporation of TIR in the GRI calculation can be seen as a potential limitation, being the only CGM parameter related to long-term complications at present [ 11 ]; however, the high correlation between TIR and GRI suggests that a similar correlation exists between GRI and the existence of long-term complications as recent studies support [ 20 , 21 ]. More studies are needed to relate this parameter to future complications, its effect on the quality of life of patients with T1D, and its evaluation in other subpopulations (T2D, hospitalized patients).…”
Section: Discussionmentioning
confidence: 99%